Dynamic Prediction Method of 3D Spatial Information of Coal Mining Subsidence Water Area Integrated with Landsat Remote Sensing and Knothe Time Function. (1st March 2022) - Liu, Hui; Li, Yu
Abstract : Subsidence water disaster has become a major problem to the ecological environment because of the submerged villages, farmland destruction, and ecological destructive changes in the mining subsidence area of high-water level. Taking the 1031 working face of Wugou Coal Mine in Huaibei, Anhui, China, as the research subject, (1) a three-dimensional (3D) spatial information dynamic prediction method was proposed for high-water-level coal mining subsidence areas by combining the Knothe time function based on the probability integration method (PIM) and the principle of water balance. (2) The dynamic evolution law of the water accumulation area in the high-water-level coal mining subsidence area was studied. (3) The applicability of the dynamic prediction model of the water accumulation range in the high-water-level coal mining subsidence area was verified. The results showed that the dynamic prediction of the 3D spatial information of the high diving area is highly accurate and can be suitable for the dynamic prediction by comparison with the results of remote sensing monitoring and field measurement. As a result, technical reference and theoretical basis for the comprehensive assessment and remediation of the ecological environment of the high diving mining subsidence area were proposed.